Professionalisation and governance in sports organisations: towards an integrated understanding - Raphael Stieger; Siegfried Nagel; Grazia Lang (Current Issues in Sport Science)
Introduction Sports organisations face increasing expectations and challenges from internal and external stakeholders. Therefore, more and more sports organisations are professionalising their structures and processes, such as establishing an executive office with paid staff, which may influence governance structures and processes. However, sports organisations may also undergo restructuring, such as reducing the board size, which can be seen as a step toward the professionalisation of governance. These examples show that professionalisation and governance are closely interrelated in practice. Sports management literature acknowledges this relationship. Shilbury and Ferkins (2011) use governance as a ‘lens’ to examine organisational professionalisation. Nagel et al. (2015) describe changes in governance structures and processes as “important consequences of professionalisation” (p. 418). The literature also calls to integrate professionalisation and governance concepts “to fully analyze the management of changes occurring within an organization” (Sharpe et al., 2018, p. 222). However, theoretical and conceptual work about the relationship of both concepts is missing to date. Therefore, this research aims to conduct a scoping review to examine the role of governance in the professionalisation of sports organisations. This study takes a first step toward a (more) integrated understanding of professionalisation and governance in sports organisations by identifying key research gaps and proposing five areas for future research. Sports practitioners are also encouraged to consider professionalisation andgovernance questions to deal with the complex relationship. This study builds on prior reviews of professionalisation (Dowling et al., 2014; Nagel et al., 2015) and governance (Dowling et al., 2018) research as its conceptual foundation.